LANGUAGE CURRICULUM AND EDUCATION IN THE POLYTECHNICAL EDUCATION: THE CASE STUDY - HRUSKOVA, Lenka; BECVAROVA, Ivana (Journal of Technology and Information Education, 2017)
The authors discuss the relationship between the ongoing transformation of technical education towards the knowledge society and the challenges that this transformation creates in association with the curriculum at a specific secondary vocational school. They present this development within the context of the specific secondary vocational school through a case study of language teaching. The case study is based on specific curricular documents and it clarifies basic concepts of the modernization of teaching process. In the same time shows innovations of principles of language teaching in the secondary sphere.
Keywords: Modernization of teaching; curriculum; foreign language teaching; general education; polytechnic education.